2020
DOI: 10.1590/s1980-220x2018034303564
|View full text |Cite|
|
Sign up to set email alerts
|

Strengthening and weakening factors for breastfeeding from the perspective of the nursing mother and her family

Abstract: Objective: To describe the strengthening and weakening factors for breastfeeding. Method: This is a descriptive multiple case qualitative study, conducted in Curitiba, Parana, with members of 17 families with children between 6 and 12 months old, through semi-structured interview and construction of genograms, analyzed by the strategy of cross case synthesis. Results: 28 people participated in the study. Strengthening factors for breastfeeding were: the desire to breastfeed; child with facility for breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 16 publications
(23 reference statements)
2
16
1
5
Order By: Relevance
“…The administrative nature, the level of complexity and the ratio of the number of professionals per bed did not in uence the offer of the complement. These ndings differ from those obtained by studies in the United Kingdom, whose lack of personnel, perception of the importance of support and professional education were associated with the offer of the complement with infant formulas [12]. However, sociocultural and biological maternal factors were protective (age) and predictors (parity and type of delivery) for such an outcome.…”
Section: Discussioncontrasting
confidence: 90%
See 4 more Smart Citations
“…The administrative nature, the level of complexity and the ratio of the number of professionals per bed did not in uence the offer of the complement. These ndings differ from those obtained by studies in the United Kingdom, whose lack of personnel, perception of the importance of support and professional education were associated with the offer of the complement with infant formulas [12]. However, sociocultural and biological maternal factors were protective (age) and predictors (parity and type of delivery) for such an outcome.…”
Section: Discussioncontrasting
confidence: 90%
“…In this study, we found a high prevalence of complement offer, which corroborates the ndings of studies conducted in other countries and in Brazilian cities [2,14,15,19]. Although the WHO recommends skin-toskin contact at birth, breastfeeding in the rst hour of life and "Do not give the newborn baby any food or drink other than breast milk, unless such procedure has a medical indication", most NB received the complement in the rst hours and days after birth.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations